Characteristics of Whale Müller Glia in Primary and Immortalized Cultures - Pereiro, Xandra; Beriain, Sandra; Rodriguez, Lara; Roiz-Valle, David; Ruzafa, Noelia; Vecino, Elena (Frontiers in Neuroscience, 2022)
Müller cells are the principal glial cells in the retina and they assume many of the functions carried out by astrocytes, oligodendrocytes and ependymal cells in other regions of the central nervous system. Müller cells express growth factors, neurotransmitter transporters and antioxidant agents that could fulfill important roles in preventing excitotoxic damage to retinal neurons. Vertebrate Müller cells are well-defined cells, characterized by a common set of features throughout the phylum. Nevertheless, several major differences have been observed among the Müller cells in distinct vertebrates, such as neurogenesis, the capacity to reprogram fish Müller glia to neurons. Here, the Müller glia of the largest adult mammal in the world, the whale, have been analyzed, and given the difficulties in obtaining cetacean cells for study, these whale glia were analyzed both in primary cultures and as immortalized whale Müller cells. After isolating the retina from the eye of a beached sei whale (Balaenoptera borealis), primary Müller cell cultures were established and once the cultures reached confluence, half of the cultures were immortalized with the simian virus 40 (SV40) large T-antigen commonly used to immortalize human cell lines. The primary cell cultures were grown until cells reached senescence. Expression of the principal molecular markers of Müller cells (GFAP, Vimentin and Glutamine synthetase) was studied in both primary and immortalized cells at each culture passage. Proliferation kinetics of the cells were analyzed by time-lapse microscopy: the time between divisions, the time that cells take to divide, and the proportion of dividing cells in the same field. The karyotypes of the primary and immortalized whale Müller cells were also characterized. Our results shown that W21M proliferate more rapidly and they have a stable karyotype. W21M cells display a heterogeneous cell morphology, less motility and a distinctive expression of some typical molecular markers of Müller cells, with an increase in dedifferentiation markers like α-SMA and β-III tubulin, while they preserve their GS expression depending on the culture passage. Here we also discuss the possible influence of the animal’s age and size on these cells, and on their senescence.